A Spectroastrometric Study of the Low-velocity Wind from DG Tau A - Yu-Ru Chou; Michihiro Takami; Shin-Ping Lai; Emma Whelan; Noah B. Otten; Min Fang; Akito Tajitsu; Masaaki Otsuka; Hsien Shang; Chun-Fan Liu; Jennifer Karr; Aisling Murphy (The Astrophysical Journal)
We obtained high-spectral resolution spectra (Δ v ∼ 2.5 km s ^−1 ) for DG Tau A from 4800 Å to 7500 Å using Subaru High Dispersion Spectrograph for the first time. The low-velocity components (LVCs, ∣ v ∣ < 100 km s ^−1 ) were observed in the [O I ] 5577, 6300, 6364 Å, [S II ] 6716, 6731 Å lines. The offset position spectra observed in a component within the LVC velocity range between –16 km s ^−1 and –41 km s ^−1 , namely, LVC-M, show a “negative velocity gradient,” supporting the presence of a wide-angled wind. With 12–70 au wind lengths measured using spectroastrometry, we estimate a lower limit to the wind mass-loss rate of ∼10 ^−8 M _⊙ yr ^−1 . In addition to the LVCs, we identify two high-velocity components (HVCs, ∣ v ∣ > 100 km s ^−1 ) associated with the collimated jet in 26 lines ([N I ], [N II ], [O I ], [O II ], [O III ], [S II ], [Ca II ], [Fe II ], H α , H β , He I ). The one with a clear spatial offset from the star ( n _e ∼ 10 ^4 cm ^−3 , HVC1) is associated with an internal shock surface of the jet, while the other at the base ( n _e ∼ 10 ^6 cm ^−3 , HVC2) may be a stationary shock component. We find that the observed line profiles and the spatial scales of the LVC emission do not agree with the existing predictions for photoevaporative or magnetohydrodynamical disk winds. These could be explained by the X-wind model, but synthetic observations are required for detailed comparisons.